Cover Picture: Highly Asymmetrical Porphyrins with Enhanced Push–Pull Character for Dye‐Sensitized Solar Cells (Chem. Eur. J. 50/2013). Issue 50 (9th December 2013) - Kurotobi, Kei; Toude, Yuuki; Kawamoto, Kyosuke; Fujimori, Yamato; Ito, Seigo; Chabera, Pavel; Sundström, Villy; Imahori, Hiroshi
<x xml:space="preserve">Abstract</x> A porphyrin π system has been modulated by enhancing the push–pull character with highly asymmetric substitution for use in dye‐sensitized solar cells. Electron injection from the porphyrin excited singlet states to a conduction band of the TiO2 electrode is very fast, whereas charge recombination is very slow, conditions ideal for high device performance. For more details see the Full Paper by V. Sundström, H. Imahori et al. on page 17075 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>